Bovine colostrum immunoglobulin concentrate for cryptosporidiosis in AIDS. Issue 4 (October 1993) - Shield, J; Melville, C; Novelli, V; Anderson, G; Scheimberg, I; Gibb, D; Milla, P
Abstract : Lactobin-R is a commercial hyperimmune bovine colostrum with potent anticryptosporidial activity. It was administered to a 4 year old child with AIDS and severe diarrhoea associated with cryptosporidiosis. There was significant clinical improvement in the diarrhoea and permanent elimination of the parasite from the gut as assessed through serial jejunal biopsy and stool specimens.